Implementation of a protocol for assembling DNA in a Teflon tube - Walsh, EJ; Feuerborn, A; Cook, PR (Society of Photo-Optical Instrumentation Engineers, 2017)
Droplet based microfluidics continues to grow as a platform for chemical and biological reactions using small quantities of fluids, however complex protocols are rarely possible in existing devices. This paper implements a new approach to merging of drops, combined with magnetic bead manipulation, for the creation of ligated double-stranded DNA molecule using "Gibson assembly" chemistry. DNA assembly is initially accomplished through the merging, and mixing, of five drops followed by a thermal cycle. Then, integrating this drop merging method with magnetic beads enable the implementation of amore complete protocol consisting of nine wash steps,merging of four drop, transport of selective reagents between twelve drops using magnetic particles, followed by a thermal cycle and finally the deposition of a purified drop into an Eppendorf for downstream analysis. Gel electrophoresis is used to confirm successful DNA assembly.